Economic Man in the Dynamics of Time and Expanse Perception - Kondratiev, Konstantin V.; Smirnov, Roman K. (Journal of History Culture and Art Research, 2017)
The article considers the issue of time perception by an economic person as an independent direction in the field of its study. The urgency of addressing this topic is conditioned, on the one hand, by the lack of its systemic coverage in literature about an economic man, and on the other hand, by the fact that the perception of time by an economic person not only develops the principles of his activity, but also influences the nature of their changes. Our study is built in accordance with the systemic, comparative-historical and dialectical method, the principle of historical and logical element unity. It is substantiated that an economic man could not appear in antiquity due to the lack of favorable conditions for his appearance, which will take shape only during the late Middle Ages and will be associated with the development of human existence secular vector. The contours of a bourgeois existence in the modern conditions of a postmodern situation are outlined. The mechanism of the bourgeois activity subordination is revealed to both linear and scattered-situational ways of time perception. The role of bourgeois activity is highlighted separately (through the transformation of the principle of uncertainty into the norm of life) in the change of the linear time model by its scattered-situational interpretation. The study concludes that A) The dialectical nature of the influence on each other concerning the way of time and bourgeois activity perception. B) The scattered-situational model of time does not mean an end, but a new stage in the history of bourgeois, whose characteristics are the following ones: the combination of features characteristic of both of modernity epoch and the epoch preceding modernity; the transformation of the market from the method of a person's personality oppression into the instrument of his self-creation.